2019
DOI: 10.3390/su11071929
|View full text |Cite
|
Sign up to set email alerts
|

Cruise Passengers’ Intention and Sustainable Management of Cruise Destinations

Abstract: Recent tourism studies have shown that cruise passengers´ intention can be used as a tool to evaluate the sustainability of port of call destination. However, studies on this topic remain scarce and only offer an initial conceptualization of this issue. Hoping to help fill this void, the present research proposes a robust model for the analysis of the cruise passengers´ intention as assessed by Partial Least Squares. Data was collected in the port of Malaga (Spain), between January and December 2018. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The whole season on the Danube lasts from the end of February to the beginning of January, the peak being from spring to autumn [30,31,47]. The starting and finishing points of the cruises are in the best position, as they have the opportunity to convince passengers to extend their stay, to get to know the destination better, and so the product can generate additional revenue for the tourist providers of the destination visited [6,48,49]. The reason for the growing popularity of river cruising is that the river environment offers not only natural beauty but also architectural attractions, and all this is accompanied by many historical and cultural experiences [50][51][52][53].…”
Section: Supply Characteristics Basic Trends Of the Cruise Industrymentioning
confidence: 99%
“…The whole season on the Danube lasts from the end of February to the beginning of January, the peak being from spring to autumn [30,31,47]. The starting and finishing points of the cruises are in the best position, as they have the opportunity to convince passengers to extend their stay, to get to know the destination better, and so the product can generate additional revenue for the tourist providers of the destination visited [6,48,49]. The reason for the growing popularity of river cruising is that the river environment offers not only natural beauty but also architectural attractions, and all this is accompanied by many historical and cultural experiences [50][51][52][53].…”
Section: Supply Characteristics Basic Trends Of the Cruise Industrymentioning
confidence: 99%
“…In the past, tourism research, the studies on the relationship among place image, emotional attitude, and behavioral intention are relatively well established [6][7][8] and the studies on the relationship between place attachment and travel intention are also common [9]. However, in the special situation of a severe epidemic like COVID-19, tourists' perceptions of destination risk have significantly changed, and the potential tourists' travel intention and decision-making processes for destinations have become more complicated and unstable.…”
Section: Introductionmentioning
confidence: 99%
“…Fernandez et al (2019) further studied cruise passengers' intention and sustainable management of cruise destinations [47]. Daniela et al (2019) confirmed that culture affects sentiments expressed in cruise tours' electronic word-of-mouth (eWOM) [48].…”
Section: Cruise Company Value Chainmentioning
confidence: 99%